LABORATORY STUDY OF POLYMERIZATION DEPTH OF COMPOSITE MATERIALS - O.A. Udod; Kh.I. Bekuzarova (Український стоматологічний альманах, 2018)
With the advent of modern improved restorative materials, the process of teeth restoration has become even more complex, but it provides an impeccable anatomical, functional and aesthetic result. In the new generation of composites there is a number of advantages, namely, increased mechanical strength, increased abrasion resistance, hardness, colour stability. All these allows restoring the anatomical shape of teeth and functional characteristics even with a significant degree of damage. However, after restoration, complications are often associated with polymerization of stress and shrinkage of composite materials, inconsistency between the coefficients of volume expansion of materials and hard tissues of teeth, etc.